2005
DOI: 10.2337/diacare.28.2.498
|View full text |Cite
|
Sign up to set email alerts
|

Possible Beneficial Effect of Telmisartan on Glycemic Control in Diabetic Subjects

Abstract: Peripheral Arterial Compliance Differs Between Races Comparison among Asian, Afro-Caribbeans, and white Caucasians with type 2 diabetes P atients with type 2 diabetes have two to three times the risk of dying prematurely from cardiovascular disease than their nondiabetic counterparts (1). Many studies have shown that arterial compliance is reduced in type 2 diabetes and that arterial stiffness increases with deteriorating glucose tolerance status, even before the onset of type 2 diabetes (2-4). In a previous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 4 publications
1
29
2
Order By: Relevance
“…Telmisartan, in addition to its blood pressure-lowering effect, has been reported to exert its antiatherogenic effect by blocking angiotensin II-induced oxidative stress and inflammation in cardiovascular tissues. 3,9,21 Furthermore, telmisartan has been reported to have an antidiabetic effect, [14][15][16][17] possibly by improving insulin sensitivity. Telmisartan, a unique ARB, has proven to be a partial PPARg agonist because of its structural similarity to thiazolidinedione derivatives, thereby improving insulin sensitivity and reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telmisartan, in addition to its blood pressure-lowering effect, has been reported to exert its antiatherogenic effect by blocking angiotensin II-induced oxidative stress and inflammation in cardiovascular tissues. 3,9,21 Furthermore, telmisartan has been reported to have an antidiabetic effect, [14][15][16][17] possibly by improving insulin sensitivity. Telmisartan, a unique ARB, has proven to be a partial PPARg agonist because of its structural similarity to thiazolidinedione derivatives, thereby improving insulin sensitivity and reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In hypertensive patients associated with T2DM and/or the metabolic syndrome, several clinical studies have shown that telmisartan has beneficial effects on glucose and lipid metabolism in addition to its antihypertensive effect. [14][15][16][17] Thus, cardiovascular protective effects of telmisartan in hypertensive patients with T2DM could be due to the combined actions of its potent blockade in the renin-angiotensin system and its partial activation of PPARg.…”
Section: Introductionmentioning
confidence: 99%
“…In both groups, there were no difference between blood pressure, fasting plasma glucose, basal insulin levels, HOMA-IR values and adiponectin levels. In several experimental and clinical studies, telmisartan and losartan have been shown to increase insulin sensitivity, reduce the occurrence of diabetes and lower fasting plasma glucose and HbA1c levels in diabetic patients (18,22,23,24,25). These two ARBs' beneficial effects on insulin resistance and glucose metabolism are due to their RAS blockade ability.…”
Section: Discussionmentioning
confidence: 99%
“…1 We first review studies in the clinical situation. There has been increasing evidence that suggests improvement in glycemic control (1,2,8,9) and favorable effects on lipid profile including reduction of LDL-cholesterol (9,10) by telmisartan administration. Quite recently, Makita et al (11) showed that telmisartan rather than candesartan may have a larger impact on obesity-related disease, demonstrating that telmisartan decreases fasting blood glucose and body weight.…”
Section: T a B L E 1 I N S U L I N S E C R E T O R Y F U N C T I O Nmentioning
confidence: 99%